Conductivity and structural studies of PVA based mixed-ion composite polymer electrolytes - Srivastava, Sandeep; K. Varshney, Pradeep (International Journal of Engineering and Technology, 2018)
The solid membranes having different ratios of poly-vinyl alcohol (PVA), sodium perchlorate (NaClO4) and lithium perchlorate (LiClO4) were prepared using solution casting technique. The mixed-ion composite polymer electrolytes were characterized by X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR) and conductivity measurement investigations. The XRD study confirms the amorphous nature of the mixed-ion composite polymer electrolytes. FTIR analysis has been used to characterize the structure of polymer which confirms the polymer and salt complex formation. The temperature dependent nature of ionic conductivity of the mixed-ion composite polymer electrolytes was determined by using conductivity meter (EC-035WP ERMA Inc, made in Japan). The ionic conductivity of the electrolyte was found in the range of 10-3 - 10-4 S/cm at room temperature.Â Â